2003
DOI: 10.1038/sj.onc.1206783
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of constitutive expression of mouse PTEN by the 5′-untranslated region

Abstract: PTEN tumor suppressor serves as a major negative regulator of survival signaling mediated by PI3 kinase/ AKT/protein kinase B pathway, and is inactivated in various human tumors. Elucidation of mechanisms responsible for PTEN expression is important for providing insight into strategies to control the loss of PTEN expression in human cancers. Although recent studies suggested that p53 and Egr-1 can modulate induced PTEN expression, the mechanism responsible for ubiquitous constitutive expression of PTEN remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 50 publications
5
67
1
3
Order By: Relevance
“…In addition to the mouse system and human cells (MEFs, HT1080, 293T 20 ), consistent significant effects have been observed in other cells and tissues, [21][22][23][24][25] (Table 1). Moorehead et al 22 observed that Egr1 is induced by and required for IGF-II-dependent induction of PTEN in the mouse mammary gland, an effect that is absent in Egr1-null mice.…”
Section: Ptensupporting
confidence: 64%
“…In addition to the mouse system and human cells (MEFs, HT1080, 293T 20 ), consistent significant effects have been observed in other cells and tissues, [21][22][23][24][25] (Table 1). Moorehead et al 22 observed that Egr1 is induced by and required for IGF-II-dependent induction of PTEN in the mouse mammary gland, an effect that is absent in Egr1-null mice.…”
Section: Ptensupporting
confidence: 64%
“…Interestingly, the function of the PTEN promoter and PTEN mRNA expression appear to be regulated by more than one transcription factor. For example, the genomic PTEN promoter sequence contains a GC-rich 5 0 untranslated region that can be activated by the transcription factor Sp1 to drive constitutive PTEN expression (Han et al, 2003). Another transcription factor, early growth response-1 (Egr-1), binds to the PTEN untranslated region and activates PTEN transcription during irradiation-induced signalling.…”
Section: Regulation Of the Pten Proteinmentioning
confidence: 99%
“…Several groups have shown that PTEN transcription may be upregulated by Early growth response-1 (Egr-1), 14 p53 15 and Sp1. 16 In contrast, NF-jB has recently been shown to inhibit PTEN transcription by a yet undetermined mechanism. 17 In 2001, 2 putative binding sites for the transcription factor peroxisome proliferator-activated receptor-gamma (PPARg) were identified about 10 kb upstream of the minimal promoter region of PTEN.…”
mentioning
confidence: 99%